Formulation and Evaluation of Pharmaceutical Suspensions Using Hemicellulose Extracted from Oil Palm Empty Fruit Bunches - Savika, Anggraini; Miswanda, Dikki; Lubis, Minda Sari; Dalimunthe, Gabena Indrayani (Indonesian Journal of Science and Pharmacy, 2025)
Oil palm empty fruit bunches (OPEFB), a major solid waste from palm oil processing, represent a rich source of lignocellulosic biomass that can be valorized into high-value bioproducts. This study aimed to isolate hemicellulose from OPEFB and evaluate its potential as a natural suspending agent in pharmaceutical suspension formulations, either alone or in combination with sodium carboxymethyl cellulose (CMC-Na). A series of formulations (F0–F5) were prepared and characterized for organoleptic properties, pH, density, viscosity, sedimentation volume, and redispersibility over seven days of storage. The results showed that suspensions containing OPEFB hemicellulose exhibited acceptable sensory characteristics, stable pH values (5–7), and densities above 1.00 g/mL. The addition of hemicellulose and CMC-Na significantly increased viscosity (up to 683.5 cP) and improved sedimentation stability, with sedimentation volumes reaching 0.22 and redispersibility up to 90% in formulations F2 and F3. These findings indicate a synergistic effect between hemicellulose and CMC-Na, enhancing suspension uniformity and preventing particle aggregation without compromising flowability. In conclusion, OPEFB-derived hemicellulose demonstrates excellent potential as a biodegradable and eco-friendly suspending agent for pharmaceutical suspensions. Its use not only improves formulation stability but also promotes the sustainable utilization of palm oil industry waste in green pharmaceutical product development. Oil palm empty fruit bunches (OPEFB), a major solid waste from palm oil processing, represent a rich source of lignocellulosic biomass that can be valorized into high-value bioproducts. This study aimed to isolate hemicellulose from OPEFB and evaluate its potential as a natural suspending agent in pharmaceutical suspension formulations, either alone or in combination with sodium carboxymethyl cellulose (CMC-Na). A series of formulations (F0–F5) were prepared and characterized for organoleptic properties, pH, density, viscosity, sedimentation volume, and redispersibility over seven days of storage. The results showed that suspensions containing OPEFB hemicellulose exhibited acceptable sensory characteristics, stable pH values (5–7), and densities above 1.00 g/mL. The addition of hemicellulose and CMC-Na significantly increased viscosity (up to 683.5 cP) and improved sedimentation stability, with sedimentation volumes reaching 0.22 and redispersibility up to 90% in formulations F2 and F3. These findings indicate a synergistic effect between hemicellulose and CMC-Na, enhancing suspension uniformity and preventing particle aggregation without compromising flowability. In conclusion, OPEFB-derived hemicellulose demonstrates excellent potential as a biodegradable and eco-friendly suspending agent for pharmaceutical suspensions. Its use not only improves formulation stability but also promotes the sustainable utilization of palm oil industry waste in green pharmaceutical product development.